Advances in enterprise engineering XII : 8th Enterprise Engineering Working Conference, EEWC 2018, Luxembourg, Luxembourg, May 28-June 1, 2018, Proceedings /: 8th Enterprise Engineering Working Conference, EEWC 2018, Luxembourg, Luxembourg, May 28-June 1, 2018, Proceedings. (2019) - Unknown
No abstract available